Epigenetic–smoking interaction reveals histologically heterogeneous effects of TRIM27 DNA methylation on overall survival among early‐stage NSCLC patients. Issue 11 (3rd September 2020) - Ji, Xinyu; Lin, Lijuan; Shen, Sipeng; Dong, Xuesi; Chen, Chao; Li, Yi; Zhu, Ying; Huang, Hui; Chen, Jiajin; Chen, Xin; Wei, Liangmin; He, Jieyu; et al.
Abstract : Tripartite motif containing 27 ( TRIM27 ) is highly expressed in lung cancer, including non‐small‐cell lung cancer (NSCLC). Here, we profiled DNA methylation of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) tumours from 613 early‐stage NSCLC patients and evaluated associations between CpG methylation of TRIM27 and overall survival. Significant CpG probes were confirmed in 617 samples from The Cancer Genome Atlas. The methylation of the CpG probe cg05293407 TRIM27 was significantly associated with overall survival in patients with LUSC (HR = 1.65, 95% CI: 1.30–2.09, P = 4.52 × 10 −5 ), but not in patients with LUAD (HR = 1.08, 95% CI: 0.87–1.33, P = 0.493). As incidence of LUSC is associated with higher smoking intensity compared to LUAD, we investigated whether smoking intensity impacted on the prognostic effect of cg05293407 TRIM27 methylation in NSCLC. LUSC patients had a higher average pack‐year of smoking (37.49LUAD vs 54.79LUSC, P = 1.03 × 10 −19 ) and included a higher proportion of current smokers than LUAD patients (28.24%LUAD vs 34.09%LUSC, P = 0.037). cg05293407 TRIM27 was significantly associated with overall survival only in NSCLC patients with medium–high pack‐year of smoking (HR = 1.58, 95% CI: 1.26–1.96, P = 5.25 × 10 −5 ). We conclude that cg05293407 TRIM27 methylation is a potential predictor of LUSC prognosis, and smoking intensity may impact on its prognostic value across the various types of NSCLC. Abstract : Among early‐stage non‐small‐cell lung cancer (NSCLC) patients, cg05293407 TRIM27 was significantly and exclusively associated with survival of lung squamous cell carcinoma patients, who had higher smoking intensity compared to lung adenocarcinoma patients. Generally, the significant association between cg05293407 TRIM27 and survival only remained in NSCLC patients having medium‐to‐high pack‐year of smoking. The cg05293407 TRIM27 ‐smoking synergistic interaction might account for histologically heterogeneous effects of TRIM27 DNA methylation on NSCLC survival.